Enhanced Platelet Aggregability under High Shear Stress after Treadmill Exercise in Patients with Effort Angina - Tokuue, Junya; Hayashi, Junichi; Hata, Yoshiya; Nakahara, Kazuhiko; Ikeda, Yasuo (Thrombosis and Haemostasis, 1996)
Platelet activation induced by shear forces occurring in a stenosed coronary artery is one of the mechanisms of coronary thrombosis. We evaluated the shear-induced platelet aggregation (SIPA) dynamics in patients with effort angina during treadmill exercise. SIPA was measured by a rotational cone-plate aggregometer. SIPA was markedly increased by exercise from 71.2 ± 8.9% to 81.9 ± 7.6% (p <0.01) in the patient group. Although epinephrine concentrations were elevated, its rate of increase was not correlated with that of SIPA. Yohimbine partially inhibited the exercise-induced increase in SIPA. In contrast, a significant correlation between the changing rate of plasma von Willebrand factor (vWF) larger multimers and that of SIPA (r = 0.74, p <0.05) was observed. Exercise-augmented SIPA is probably dependent on an increase in vWF larger multimers rather than platelet alpha2-receptor activation. Prevention of the interaction between vWF and its platelet receptors may play some role in decreasing the risk of coronary thrombosis during exercise.